ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DALAM MEMBENTUK NIAT BELI ULANG - Gatot Wibowo, Marjam Desma Rahadhini & Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
Aim of this research are to explain 1,2) influence of product quality and servicequality to customer satisfaction; 3,4) explaining product quality and service quality tocustomer satisfaction and 5) customer satisfaction to re-purchase intention.Thisresearch is conducted at Rumah Makan Pecel Solo branch Solo. Sample measurement isused as 135 respondents with non-probability sampling tekhnique and purposivesampling method. Data analysis technique used is Structural Equation Modelinganalysis technique. Research result indicates that there is influence of significantproduct quality and service quality toward customer’s satisfaction; product quality andservice quality give influence significant to repurchase intention; and customersatisfaction influence significant to repurchase intention. Based on aim of research,suggestion for the management of Rumah Makan Pecel Solo, is to improve the quality ofservices and maintain the quality of their products in order to provide total satisfactionto the consumer and the impact to the strong of re-purchase intention.Keywords: product quality, service quality, customer satisfaction, re-purchase intentions